Pertumbuhan ekonomi kota dan pengaruhnya terhadap kesempatan kerja di Kota Jambi - Parmadi, Parmadi; Hari Prihanto, Purwaka; Ratnawati, Rts. (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze, 1) City economic growth and employment opportunities in Jambi city; 2) Effect of urban economic growth on employment opportunities in Jambi city. The data used are time-series data from 2010-2018, derived from microdata from the Jambi Province National Labor Force Survey (SAKERNAS) and GRDP data. The results showed; 1) The average economic growth of the city of Jambi in the period 2010 - 2018 was 5.7 percent, while employment opportunities experienced an average growth of 3.2 percent, 2). Estimation results with simple regression indicate a significant effect between GRDP growth on employment opportunities in Jambi city